Bacillus Calmette-Guérin vaccine-induced lupus vulgaris in a child - Najem, Nabeel M. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Lupus vulgaris (LV) is a rare form of cutaneous mycobacterial infection in children. Most cases follow hematogenous or lymphatic seeding, and more rarelyfrom exposure to bacillus Calmette- Guerin (BCG) vaccine. We report a child that received BCG vaccination and developed LV 2 months later.
Keywords: Adverse Effects; bakterijske infekcije; BCG cepivo; BCG Vaccine; cepljenje; Child; kožne spremembe; lupus vulgaris; otroci; Otrok